2022
DOI: 10.1039/d2ea00003b
|View full text |Cite
|
Sign up to set email alerts
|

Emerging investigator series: surfactants, films, and coatings on atmospheric aerosol particles: a review

Abstract: Surfactants are surface-active molecules or ions that can often be found at the surface of atmospheric aerosol particles. Some surfactants, such as biomolecules in marine aerosol and cooking oils in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 505 publications
0
26
0
Order By: Relevance
“…Ionic strength could also affect PO multiphase transformation pathways by providing a higher concentration of electrolytes in the aqueous phase, which could hinder the dissociation of reaction intermediates and shift the equilibrium. , Recent evidence showed that the photochemical and photocatalytic kinetics can be significantly accelerated by moving from the bulk phase to microdroplets, which further exhibited a size-dependent acceleration . Extended effective surface area, unique air–water interfacial properties, light enrichment, and imhomogeneous distribution of reactive species (e.g., proton) have been proposed to characterize aerosol/droplet chemistry. , In return, it also remains largely unknown how the multiphase reaction pathways of POs can vary the interfacial properties of aerosol as well as microdroplets. , In the future, investigations on these factors and other properties are needed when designing experiments to understand PO multiphase transformation pathways under atmospherically relevant conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ionic strength could also affect PO multiphase transformation pathways by providing a higher concentration of electrolytes in the aqueous phase, which could hinder the dissociation of reaction intermediates and shift the equilibrium. , Recent evidence showed that the photochemical and photocatalytic kinetics can be significantly accelerated by moving from the bulk phase to microdroplets, which further exhibited a size-dependent acceleration . Extended effective surface area, unique air–water interfacial properties, light enrichment, and imhomogeneous distribution of reactive species (e.g., proton) have been proposed to characterize aerosol/droplet chemistry. , In return, it also remains largely unknown how the multiphase reaction pathways of POs can vary the interfacial properties of aerosol as well as microdroplets. , In the future, investigations on these factors and other properties are needed when designing experiments to understand PO multiphase transformation pathways under atmospherically relevant conditions.…”
Section: Discussionmentioning
confidence: 99%
“…421,477 In return, it also remains largely unknown how the multiphase reaction pathways of POs can vary the interfacial properties of aerosol as well as microdroplets. 478,479 In the future, investigations on these factors and other properties are needed when designing experiments to understand PO multiphase transformation pathways under atmospherically relevant conditions. 8.2.6.…”
Section: Po Hydrolysismentioning
confidence: 99%
“…The term “surfactant” comes from “surface active agents”, which are molecules that adsorb on the water–surface interface and reduce water’s surface tension to enhance the cleaning of surfaces. , They are also known as amphiphiles because they have polar heads, also known as hydrophilic heads, that have an attraction for polar solvents, and nonpolar tails, also known as hydrophobic tails. , The molecular structures of these molecules help reduce the cohesive forces between water molecules, resulting in the lowering of surface tension. They possess other qualities that allow them to be used in applications other than lowering surface tension , such as emulsifiers, foaming agents, corrosion inhibitors, and antistatic agents. Surfactants have been used in practically every industry because of their physicochemical characteristics . These include paints, inks, , coatings, adhesives, paper and pulp, petroleum and oil, plastics, resins, textiles and fibers, detergents, agricultural, food, cosmetics, pharmaceutical, and various industrial applications . Originally, surfactants were only created from renewable resources such as plant oils or animal fat.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their amphiphilic nature, organic acids tend to partition to the gas−aerosol interface, reducing the surface tension of the particle, affecting cloud formation, and potentially forming a physical barrier to gas uptake. 5,6 While the barrier effect is most pronounced for long-chain fatty acids which have strong interactions among the tail groups of neighboring molecules, small, semivolatile amphiphilic species have also been shown to partition to the gas−aerosol interface, impacting aerosol properties. 7 The smallest organic acids, formic acid (HCOOH) and acetic acid (CH 3 COOH), constitute a quarter of nonmethane organics in the atmosphere.…”
Section: ■ Introductionmentioning
confidence: 99%